The role of novice physical sciences teachers’ goals in the implementation of inquiry-based instruction - Sebenzile Ngema; Angela James; Doras Sibanda (Cogent Education)
Research has extensively documented the benefits of inquiry-based science teaching, but less attention has been paid to how novice teachers’ personal teaching goals influence their implementation of this approach. This study aimed to explore novice physical sciences teachers’ goals to understand how they relate to IBI implementation. This research focused on three novice physical sciences teachers, employing a qualitative, multiple-case study design. Data gathering methods included open-ended questionnaires administered at the beginning of the study, classroom observations conducted over two semesters, and in-depth-stimulated interviews to gain insight into teachers’ thinking about their goals and IBI implementation. The findings revealed a direct relationship between IBI and teachers’ goals during classroom practice. Physical sciences teachers rely more on traditional teaching methods and have difficulty incorporating IBI into their classrooms. The teacher with a guided inquiry goal implements IBI at a proficient level, and those with an active direct goal implement IBI at a developing inquiry level. The findings suggest successful IBI implementation depends on acknowledging and incorporating novice teachers’ goals in their developmental programmes.